Morphometric study of the size of the postmortem human kidney - Johora, Fatema; Nurunnabi, Abu Sadat Mohammad; Siddiqua, Dilruba; Hena, Hasna; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2020)
Background: Changes in the size of the kidney are evident in humans, as age progresses. Objective: To see the age-related changes in the morphological dimensions of the kidney in a sample of the Bangladeshi population. Methods: This crosssectional study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, based on a collection of 140 postmortem human kidneys collected from 70 unclaimed dead bodies from the morgue of the same institution. All the samples of kidney were divided into three age groups, including A (10-19 years), B (20-39 years) and C (40-59 years). The length, breadth and thickness of all the kidneys were measured by using a slide calipers and recorded. Data were expressed as mean±SD. For statistical analysis, independent sample t test and one way ANOVA was used. Results: The length of the right and left kidneys found were 8.72±0.25 cm and 9.28±0.12 cm; 9.73±0.35 cm and 10.31±0.41 cm; 9.68±0.21 cm and 10.24±0.06 cm in group A, B and C respectively. The breadth of the right and left kidneys found were 4.32±0.09 cm and 4.22±0.11 cm; 4.74±0.29 cm and 4.55±0.28 cm; 4.61±0.21 cm and 4.44±0.21 cm in group A, B and C respectively. The thickness of the right and left kidneys found were 2.84±0.10 cm and 2.64±0.05 cm; 3.31±0.16 cm and 3.11±0.10 cm; 3.17±0.07 cm and 3.11±0.10 cm in group A, B and C respectively. The mean length of the left kidneys was found significantly greater than that of the right , whereas the mean breadth and the thickness of the right kidneys were found greater than that of the left kidney in all age groups. Moreover, age related changes were significant in all dimensions (length, breadth and thickness) of the kidney when compared between group A & B and A & C. Conclusion: This study results concluded that the length of the left kidney was greater than that of the right, but the breadth and the thickness of the right kidney were greater than that of the left one in all age groups. In addition, age related changes in all dimensions (i.e. length, breadth and thickness) of the kidneys were evident in middle age versus young adult and older adult versus young adult. J Bangladesh Soc Physiol. 2020, December; 15(2): 61-67